Organoleptic Evaluation of Kepok Banana Heart (Musa Paradisiaca Normalis) Nugget with Added Catfish - Sineke, Jufri; Purba, Rudolf Boyke; Paruntu, Olga Lieke; Montol, Ana B; Rangka, Nada Sofia (Universitas Airlangga, 2023)
Food is defined as something that can be eaten by humans. In terms of consuming food, it is important to pay attention to the diversity of types of food, so that nutrients can be fulfilled. Banana heart has a very high fiber content. The types of banana buds used in this study were kepok banana buds. Catfish contains high nutritional value and used as a source of protein. This study aims to determine the organoleptic evaluation of kepok banana heart nuggets with addition of catfish including color, aroma, texture, and taste. The research design was a quasi-experimental experiment with three treatments using a comparison of banana heart kepok and catfish meat, as followP1 (banana heart 250 g and catfish 100 g), P2 (banana heart 200 g and catfish 50 g), and P3 (banana heart 150 g fish and catfish 25 gr). The results of the color test showed that the highest results were 100% like to very much like P1 and P2, aroma 100% like to very much like P2 and P3, texture 100% like to very much like P2 and taste 100% like very much like is at P2. The results of the different test analysis showed differences in color, aroma, texture, and taste in the three treatments with a p-value = 0.000. In conclusion, treatment 2 is most preferred formulation by panelists, with a ratio of 200 banana heart and 50 g catfish.